Post-fall reporting in aged acute inpatient mental health units: an 18-month observational cohort study. (4th September 2017) - Furness, Trentham; Mnatzaganian, George; Garlick, Robyn; Ireland, Susan; McKenna, Brian; Hill, Keith D.
ABSTRACT: Background: Despite the high risk of falling for people with severe mental illness, there is limited falls research in mental health settings. Therefore, the objective of this observational cohort study was to conduct a focused post-fall review of fall episodes within aged acute inpatient mental health units at one of Australia's largest publicly funded mental health organizations. Methods: A post-fall reporting tool was developed to collect intrinsic and extrinsic fall risk factors among three aged acute mental health inpatient units over an 18-month period. Descriptive and inferential analyses were conducted to describe fall risk factors and predictors of fall risk. Results: There were a total of 115 falls, of which the tool was used for 93 (80.9%) episodes. Falls occurred most often in consumer's bedroom/bathroom and were unwitnessed. Intrinsic risk factors were most often attributed to postural drop and losing balance during walking. However, that was in contrast to consumer's who self-reported feeling dizzy as the reason of the fall. Conclusions: Based on the cohort, future falls could be reduced by targeting those aged above 82 years, or with a diagnosis of dementia. Recurrent falls during admission could be reduced by targeting those with psychotic illness and males with a diagnosis of dementia. A clearer dialogue among consumers and clinical staff reporting about fall episodes may support future remedial interventions and inform programs to reduce fall risk and assist the challenge of describing unwitnessed falls in aged acute inpatient mental health settings.